Psychometric properties of the Smartphone Addiction Scale (SAS-SV) in adolescents in Peru - Joel Figueroa-Quiñones; Julio Cjuno; Wilter C. Morales-García; Saulo Salinas-Arias (Humanities & Social Sciences Communications)
Abstract To evaluate the structural validity, reliability, and measurement invariance of the Smartphone Addiction Scale in Peruvian adolescents. 1274 adolescents of both sexes, between 12 and 17 years old, residing in the cities of the coast (Chimbote), mountains (Cajamarca), and jungle (Tarapoto) of Peru were evaluated. A confirmatory factor analysis was performed, and the measurement invariance according to age, region, and sex was evaluated using MIMIC (Multiple Indicator, Multiple Cause) models. Reliability was estimated through the Omega coefficient. A two-factor, 10-item model was obtained with optimal goodness-of-fit indices (CFI = 0.990; TLI = 0.986; SRMR = 0.04; RMSEA = 0.08). MIMIC models reported invariance for age groups, sex, and region (ΔCFI < 0.01, ΔRMSEA < 0.01). Reliability was optimal (>0.79). Conclusion: The Peruvian version of the Smartphone Addiction Scale (10 items) has shown adequate psychometric properties for use in the adolescent population.